Activated Carbon from Pepper Waste for Heavy Metals Adsorption - Nur Ezzati, Binti Arshad (Universiti Malaysia Sarawak (UNIMAS), 2015)
In this study, the ability of activated carbon (AC) from Piper nigrum waste to remove lead (Pb), iron (Fe) and zinc (Zn) from aqueous solution was investigated. The AC was prepared by using chemical activation process. The Scanning Electron Microscope (SEM) images showed that the carbon before activation has less pores compared to carbon after activation. The performance of AC was studied by varying the adsorbent dosage, initial metals concentration, and agitation time on the metals removal. The adsorption ability of pepper waste based AC was compared with adsorption ability of commercial activated carbon (CAC). Pepper waste based AC showed a favorable result where it was able to adsorb Pb and Fe metals up to 89.9% and 46.0%, respectively. Zn metals adsorption does not show a good result where it only adsorbed 31.4%. The study also showed that the removal efficiency of the pepper waste based AC was greatly affected by the adsorbent dosage and initial metal concentrations while contact time showed less dependency. The use of pepper waste as AC can help to overcome the abundance of pepper waste and can be used as a low cost material for water treatment.